A conceptual approach to dynamic land-use modelling - Thornton, Philip K.; Jones, Peter G. (Elsevier, 1998)
A dynamic agriucltural land-use model based on a Markov process and governed by a few simple decision rules is described. Currently, the model is purely conceptual, and was designed with one objective: to investigate the possibility of constructing top-down land-use models based on as few processes as possible that might still be useful for statistical analyses of land-use change in a region. The model appears to behave in a plausible fashion in a simulated landscape with respect to cropping patterns and the effects of initial household size on wealth distribution. If this type of simple model could be validated, the information that could be produced might be of considerable value in a wide range of applications, particularly with regard to technology adoption patterns and resultant regional production impacts.